The development and capitalizing possibilities of the tourism and agrotourism in Tulcea County - Eugenia Dorina Rădoi; Petruța Antoneta Turek-Rahoveanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
Tulcea county is a very important touristic aria of our country, because it is the gate to the Danube Delta Biosphere Reservation, the place where the Danube devides in 3 arms and pours into the Black Sea, forming here a real corner of heaven with dreamlike landscapes and full of life, the third place of ecological importance in the world. Across the county there is a municipality, 5 cities, 46 parishes and 133 villages, which means that this is mainly a rural area. The living standard of the rural area inhabitants from here is not a very good one, poverty being the problem the county inhabitants are confronting for years, despite the tourism potential of the area which is not capitalized properly. This paper wants to highlight the problems that limit the tourist activity in this area that has a great potential in this regard and aims to also highlight a few posibilities of development and capitalizing of the tourism potential, by making a touristic and agrotouristic quality activity.
Keywords: 330; agrotourism; tourism potential; touristic activity